CIA sexpionage - Piligian, Craig; Melton, H. Keith; David Harris; Cary, Michael; Engman, Paul (distributed by Discovery Channel Video ; distributed in the Philippines by MagnaVision, 2004)
If it is true that espionage is the second oldest profession in the world, it only makes sense that it would draw on the oldest to learn a few lesons. In "CIA Sexpionage", viewers are drawn into a world where operatives use sex to steal secrets from potential adversaries. Viewers will see how some of the greatest secrets of the Cold War were lost as leaders of countries fell prey to cold and calculated spies using sex as a weapon. Cold War footage warning CIA operatives and military personnel of the dangers entrapment by KGB operatives using sex as a tool will astound. We learn of some of these operations ann, through Discovery Channel's exclusive connection to the spy world, actually talk to some of the greatest living spies involved in actual operations. We'll meet the male "Romeos" and female "Swallows" that were selected and trained to use sex to obtain secrets.